Characteristics of Foreign R&D Strategies of Swiss Firms. Implications for Policy - Heinz Hollenstein (Austrian Institute of Economic Research (WIFO), 2008)
The aim of the paper is, firstly, to identify a number of strategies Swiss firms pursue by performing foreign R&D, expecting that firms, in many instances, are driven by a combination of several motives ("mixed strategies"). Secondly, we ask whether foreign and domestic R&D are substitutes or complements. Thirdly, we draw some policy conclusions based on results for direct and indirect home-country effects of foreign R&D. By applying cluster analysis, we identified four specific patterns of motives of foreign R&D. In a second step, we investigated whether these clusters effectively may be interpreted as specific types of R&D strategies. To this end, the clusters were characterised in terms of a large number of variables, which, according to the OLI paradigm of FDI, determine foreign R&D. We found that the patterns of the four clusters systematically differ with respect to these theory-related variables. Some clusters represent, in terms of motives, broad-based mixed strategies, whereas others are strongly focused. It turns out that foreign R&D strategies that primarily aim at exploiting capabilities of the domestic headquarters dominate, whereas cost-reducing strategies are of very minor importance. In case of the other two strategies knowledge sourcing is a constituent element, in the first one, knowledge sourcing is at the core, in the second case it is an important element in the frame of a broad-based strategy. The relative importance of the four strategies implies that, on balance, foreign and domestic R&D are complements. Notwithstanding this positive result, it is sensible to take policy actions supporting the economy to capitalise even more on outward FDI in R&D. Policy basically should aim at securing the attractiveness of Switzerland as a location for R&D-intensive headquarters of firms performing foreign R&D, and at enhancing knowledge spill-overs from headquarter companies to other domestic firms. The five categories of measures we recommend are part of a framework-oriented policy design rather than of a more interventionist concept.
Keywords: 330; Internationalisation of R&D; Motives of foreign R&D; Foreign R&D strategies; Knowledge spillovers; Home-country effects of outward FDI in R&D; Industrieforschung; Im Ausland; Wissenstransfer; Wirkungsanalyse; Technologiepolitik; Schweiz